2022
DOI: 10.1016/j.joca.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis year in review: genetics, genomics, epigenetics

Abstract: Summary Objective In this review, we have highlighted the advances over the past year in genetics, genomics and epigenetics in the field of osteoarthritis (OA). Methods A literature search of PubMed was performed using the criteria: “osteoarthritis” and one of the following terms “genetic(s), genomic(s), epigenetic(s), polymorphism, noncoding ribonucleic acid (RNA), microRNA, long noncoding RNA, lncRNA, circular RNA, RNA sequencing (RNA-seq), single cell seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…In response to environmental and metabolic activities, epigenetic processes regulate the modulation of gene expression via microRNA regulation, DNA methylation, or histone modification [ 28 , 37 ]. Furthermore, previous studies have proven that TSA, an epigenetic modifier has a beneficial effect on bone repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In response to environmental and metabolic activities, epigenetic processes regulate the modulation of gene expression via microRNA regulation, DNA methylation, or histone modification [ 28 , 37 ]. Furthermore, previous studies have proven that TSA, an epigenetic modifier has a beneficial effect on bone repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing interest in competing endogenous RNAs (ceRNAs), such as circular RNAs (circRNAs) and long ncRNAs (lncRNAs), which act as miRNA sponges, although the physiological significance of ceRNAs is not well understood. Several ncRNAs have been reported to be involved in cartilage development and homeostasis [ 66 ].…”
Section: Ncrnas Involved In Cartilage Homeostasis and Oamentioning
confidence: 99%
“…The most typical symptoms of osteoarthritis are mechanical pain, joint abnormalities and swelling, limitation of range of movement, joint stiffness, and motion cracks. Flaring phases with dominant inflammation, which are commonly characterized by joint swelling, a fast escalating pain, discomfort at rest, and increased stiffness, might impede the natural development of OA [2,11,12]. According this study, we demonstrated the role of GDF15 in OA.…”
Section: Discussionmentioning
confidence: 56%
“…Chondrocytes are the only cells found in the cartilage tissue and play a crucial role in maintaining cartilage stability. Chondrocytes undergo various alterations throughout the onset and progression of OA, including changes in their proliferation, viability, and secretion [2]. OA is considered a multifaceted illness affecting the entire joint rather than only the cartilage or synovium.…”
Section: Introductionmentioning
confidence: 99%